Real‐world use of first‐generation antiandrogens: impact on patient outcomes and subsequent therapies in metastatic castration‐resistant prostate cancer. Issue Volume 128:Issue Supplement 1(2021) (7th October 2021) - Kelly, Richard; Anton, Angelyn; Wong, Shirley; Shapiro, Julia; Weickhardt, Andrew; Azad, Arun; Kwan, Edmond Michael; Spain, Lavinia; Muthusamy, Arun; Torres, Javier; Parente, Phillip; Parnis, Francis; et al.
Abstract : Objectives: To investigate the recent real‐world use of first‐generation antiandrogens (FGAs) in metastatic castration‐resistant prostate cancer (mCRPC) using a retrospective multicentre cohort study. Patients and Methods: The electronic CRPC Australian Database (ePAD) was interrogated to identify patients with mCRPC. Clinicopathological features, treatment and outcome data, stratified by FGA use, were retrieved and reported through descriptive statistics. Survival analyses were calculated using the Kaplan–Meier method and groups compared using log‐rank tests. Factors influencing overall survival (OS) were analysed using Cox proportional hazards regression model. Results: We identified 634 patients with mCRPC, enrolled in ePAD between January 2016 and March 2019, including 322 (51%) who received FGAs. The median follow‐up was 21.9 months. Patients treated with FGAs were more likely to have lower International Society of Urological Pathologists (ISUP) grade group ( P = 0.04), longer median time to CRPC (25.6 vs 16.0 months, P < 0.001), and were less likely to have visceral metastases (5.0% vs 11.2%, P = 0.005) or to have received upfront docetaxel ( P < 0.001). A ≥50% reduction from pre‐treatment prostate‐specific antigen (PSA) level (PSA50 response) during FGA treatment occurred in 119 (37%) patients and was independently associated with improved OS (hazard ratio 0.233, P < 0.001). Prior FGA treatment did not significantly influence the selection of subsequent life‐prolonging treatments for mCRPC or their PSA50 response rates. Conclusion: In our present cohort, FGAs were commonly used in lower‐risk mCRPC and their use did not significantly influence the choice or duration of subsequent systemic therapy. A PSA50 response to FGA therapy was an independent favourable prognostic marker associated with improved OS.